Using Velocity Anisotropy to Analyze Magnetohydrodynamic Turbulence in Giant Molecular Clouds - Madrid, Alecio (Proceedings of the Wisconsin Space Conference, 2018)
Theoretical studies have shown structure function (SF) analysis to be a strong tool for gaging interstellar magnetohydrodynamic (MHD) turbulence. MHD turbulence plays a critical role in the structure and evolution of giant molecular clouds (GMCs) as well as in the formation of sub-structures known to spawn stellar progenitors. This study takes an in-depth approach to studying the limitations of SF analysis for gauging MHD turbulence in GMCs. Limitations of radio observation has led to large variations in the methods used to extract GMCs from survey data. Thus, a strong indicator of the robustness of SF analysis is whether it remains accurate even when implementing different methods of extraction. Even though a plethora of studies have indicated the strong potential of SF for analyzing MHD turbulence, this study finds significant cause for concern regarding the feasibility of SF analysis as a robust tool in GMC spectroscopy.